The Correlation of Hemodynamic Status and Oxygen Saturation with The Level of Consciousness in Head Injury Patients - Nuril Kumalasari; Marsaid; Lingling Marinda Palupi (Babali Nursing Research, 2020)
Introduction: Head injury is a traumatic disorder caused by the mechanical strength of a blunt object or penetration that can cause temporary or permanent changes in tissue function and structure. The latest developing concept on poor prognosis among head injury patients was occur related to the secondary injuries, where there was an increase in intracranial, cerebral ischemia, and decreased consciousness. The important thing in the management of head injuries is to maintain hemodynamic stability and to prevent hypoxia by maintaining oxygen saturation >95%. The purpose of this study was to analyze the correlation of hemodynamic status and oxygen saturation with the level of consciousness in head injury patients at RSUD Mardi Waluyo, Blitar. Methods: The research used correlational analytical with a cross-sectional design. The sampling technique used consecutive sampling within a total sample of 30 respondents. Spearman's test was used for data analysis. Results: The results showed a correlation between mean arterial pressure (p-value = .004), respiratory rate (p-value = .000), body temperature (p-value = .017), and oxygen saturation (p-value = .000) with level of consciousness (GCS) respectively. Conclusion: It can be concluded that mean arterial pressure, respiratory rate, body temperature, and oxygen saturation can affect the level of consciousness (GCS). There was a need to improve hemodynamic and oxygen saturation monitoring to prevent the bad prognosis in head injury patients at RSUD Mardi Waluyo, Blitar.